2018
DOI: 10.33964/jp.v27i2.376
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Model Pertanian Ramah Lingkungan sebagai Jaminan Perbaikan Kuantitas dan Kualitas Hasil Tanaman Pangan

Abstract: Keberhasilan peningkatan produktivitas tanaman pangan yang diikuti dengan kelestarian lingkungan hidup merupakan prinsip penerapan sistem pertanian ramah lingkungan berkelanjutan. Berbagai sistem pertanian ramah lingkungan telah dikembangkan dengan berpedoman pada budidaya pertanian yang baik melalui sinergis antar komponen teknologi, antara lain pengelolaan tanaman terpadu, jajar legowo super, sistem integrasi tanaman-ternak bebas limbah, dan pengendalian organisme pengganggu tanaman secara terpadu. Melalui s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 2 publications
0
10
0
12
Order By: Relevance
“…Sistem tanam jajar legowo adalah sistem tanam padi dengan jarak dan tata tanam berselang seling antara dua atau lebih (sistem tanam yang direkomendasikan adalah 2:1, 3:1 dan 4:1) barisan tanaman dan diselingi satu barisan yang kosong, dimana jarak tanam pada barisan pinggir setengah kali jarak tanam antarbarisan (Kementerian Pertanian 2016;Rebekka 2018). Sistem tanam jajar legowo 2:1 dengan jarak tanam 25 cm x 12,5 cm x 50 cm meningkatkan populasi tanaman 33,3% dibanding sistem tanam tegel dengan jarak tanam 25 cm x 25 cm (Wihardjaka 2018). Prinsip sistem tanam jajar legowo adalah memanipulasi sebagian besar letak rumpun tanaman padi agar berada di pinggir barisan (tanaman pinggir) agar tanaman memperoleh sinar matahari lebih banyak sehingga menghasilkan kuantitas dan kualitas gabah lebih baik (Ikhwani et al 2013), memudahkan pemupukan, pengendalian gulma, dan menekan perkembangan penyakit endemik karena kelembaban yang tinggi (Kementerian Pertanian 2016).…”
Section: Pendahuluanunclassified
“…Sistem tanam jajar legowo adalah sistem tanam padi dengan jarak dan tata tanam berselang seling antara dua atau lebih (sistem tanam yang direkomendasikan adalah 2:1, 3:1 dan 4:1) barisan tanaman dan diselingi satu barisan yang kosong, dimana jarak tanam pada barisan pinggir setengah kali jarak tanam antarbarisan (Kementerian Pertanian 2016;Rebekka 2018). Sistem tanam jajar legowo 2:1 dengan jarak tanam 25 cm x 12,5 cm x 50 cm meningkatkan populasi tanaman 33,3% dibanding sistem tanam tegel dengan jarak tanam 25 cm x 25 cm (Wihardjaka 2018). Prinsip sistem tanam jajar legowo adalah memanipulasi sebagian besar letak rumpun tanaman padi agar berada di pinggir barisan (tanaman pinggir) agar tanaman memperoleh sinar matahari lebih banyak sehingga menghasilkan kuantitas dan kualitas gabah lebih baik (Ikhwani et al 2013), memudahkan pemupukan, pengendalian gulma, dan menekan perkembangan penyakit endemik karena kelembaban yang tinggi (Kementerian Pertanian 2016).…”
Section: Pendahuluanunclassified
“…The traditional farming system is characterized by pest and disease management was done by using chemical pesticide intensively without considering the Integrated Pest Management (IPM) principals. Excessive use of chemical pesticide created many negative effects such as the increasing of farming system cost, un-optimum crops productivity, environmental pollution, the presence of pesticide residues in fruits or vegetables after and during harvest, pest become resistant to pesticides, the destruction of biodiversity, lead to secondary pest outbreaks and harmful to human health [2,3,4,5,6,7]. Furthermore, farmers in Bali Province have not applicated yet the balanced fertilization, they only applicated the chemical fertilizer for their farming system.…”
Section: Introductionmentioning
confidence: 99%
“…The ICM implementation is emphasizing on farmer active participation to choose and evaluate appropriate technology for their biophysical environment, socialcultural, and economic aspect. The implementation of ICM is not only solely purposed to maximizing yields but also environmentally sustainable while increasing production efficiency and profitability [7,11,10,12]. Many studies have reported the successful of ICM implementation to increase the productivity of crops and farmer's income particularly to the food crops and horticulture commodity such as rice, maize, and cayenne pepper [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, an environmentally friendly agricultural system is a sustainable agricultural system that aims to increase and maintain high productivity by paying attention to the supply of nutrients. This system uses organic materials, minimizes inorganic fertilizers, improves soil biota, controls plant pest organisms (OPT) based on ecological conditions, and diversifies crops [5]. One of the obstacles in cultivating shallots in production centers is the high use of chemical fertilizers and pesticides.…”
Section: Introductionmentioning
confidence: 99%